Crony capitalism through political distortions amongst publicly listed firms in China - Liew, Andy He Wen (Nanyang Technological University, 2020)
This final year project examines for evidence of crony capitalism in China by investigating if politically distorted firms receive lower cost of capital. We make use the detailed information of publicly listed firms in China’s stock market over the period of 2008 to 2015. Political distortions are captured through two measures: (1) firm ownership type, as standard in the existing literature; and (2) political connection of top management, a novel contribution of this research. Our identification comes from two sources. First, using a fixed-effect model, we find that all else being equal, state-owned enterprises and chairperson political connections lower a firm’s cost of capital. Second, from a difference-in-difference strategy, we find that during China’s 2008 stimulus, state-owned enterprises crony capitalistic benefits intensified through even lower cost of capital. These findings are important as such capital misallocation lowers China’s total factor productivity.